MLN2238 synergizes BH3 mimetic ABT-263 in castration-resistant prostate cancer cells by induction of NOXA - Wei, Xinghua; Zhou, Ping; Lin, Xuanting; Lin, Yurong; Wu, Sifeng; Diao, Pengfei; Xie, Haiqing; Xie, Keji; Tang, Ping (Tumor biology, 2014)
Patients undergoing androgen blockade therapy develop castration-resistant prostate cancer (CRPC), which is associated with Bcl-2 upregulation and results in disease progression and death. In recent years, promising therapeutic agents, such as the BH3-only mimetic ABT-263 and proteasome inhibitors, have been developed and widely evaluated against a broad spectrum of cancer types, including prostate cancer, alone or in combination with other chemotherapeutic agents. In this study, the antitumor efficacy of ABT-263 and MLN2238 were evaluated as single agents and in combination in four CRPC cell lines: PC3, C4-2B, C4-2, and DU145. The viability of the treated cells and markers of apoptosis were assayed. Protein-protein interactions were analyzed by co-immunoprecipitation in drug-treated cells. Lentivirus-mediated short hairpin RNA was used to knockdown Bax, Mcl-1, and NOXA expressions. We found that ABT-263 and MLN2238 alone exhibited a mild cytotoxicity, and in combination, they elicited a synergistic cytotoxic effect in CRPC cells. The cell apoptosis induced by the combination drug treatment was evidenced by enhanced caspase-3 and Poly (ADP-ribose) polymerase (PARP) cleavage, and annexin-V-positive staining was significantly depleted by Bax knockdown. MLN2238 treatment upregulated NOXA and Mcl-1 expression, leading NOXA/Mcl-1 complexes to disassociate Bak from its complexes with Mcl-1 and enhancing ABT263-triggered Bax activation. NOXA knockdown by short hairpin RNA significantly attenuated the cytotoxicity of ABT-263 and MLN2238 co-administration. In conclusion, MLN2238 and ABT-263 synergistically triggered apoptosis in CRPC cells by upregulating NOXA and activating Bax, indicating a promising therapeutic strategy for the treatment of CRPC.